PERBEDAAN RATA-RATA JUMLAH PEMBIAYAAN, KUALITAS PEMBIAYAAN DAN PENDAPATAN MARGIN MURABAHAH BANK SYARIAH SEBELUM DAN SESUDAH PERUBAHAN BI RATE - Darna, Darna; Ramadhani, Widianti Indah; Nasution, Mulia (Ekonomi & Bisnis, 2015)
Abstract BI rate is a monetary policy which targeting to inflation in the end. The impact of monetary policy are vast and the impact of the change of BI rate is very large and wide, especially for the banking sector. The possibility of Islamic Banking affected by this change of BI rate was also there although it may be very small and indirect. This research aimed to analyze the differences in the average of the financing, murabahah margin and NPF ratio caused by changes of BI rate by Bank Indonesia as the Central Bank while the Islamic Bank Financing does not use the system of interest. Beside that, this research also analyze the impact of this changes to the Islamic Bank. This research took the form of cross section data of Islamic Bank's financial statements in the first quarter of 2013 as the period before the change of BI rate and the first quarter of 2014 as the period after the change of BI rate. The variables used were total financing, the ratio of the NPF as a ratio which described quality of Sharia Bank’s financing and murabahah revenue margins. Techniques of data collection is through documentation and interviews as a support of the research’s hypothesis. Source of data obtained from published financial statements of Islamic Bank on Bank Indonesia’s official website. The data were analyzed using paired samples t test. Based on the results, it revealed that there are differences in average of total murabahah revenue margin and total financing that Sharia Bank gave before and after the change of BI rate. While there is no difference in the average of NPF ratio before and after the change of BI rate. Keywords: BI rate, Financing, NPF, Financing Margin, Islamic Bank.. Abstrak BI rate adalah sebuah kebijakan moneter dengan sasaran akhir inflasi. Dampak yang ditimbulkan oleh kebijakan tersebut sangatlah luas dan perubahan BI rate ini amatlah besar dan luas dampaknya terutama bagi sektor perbankan. Kemungkinan Bank Syariah terkena dampak dari perubahan BI rate ini pun juga ada meskipun mungkin sangatlah kecil dan secara tidak langsung. Penelitian ini bertujuan untuk menganalisa perbedaan rata-rata dari pembiayaan, rasio NPF dan margin pembiayaan yang ditimbulkan oleh perubahan suku bunga acuan oleh Bank Indonesia sebagai Bank Sentral terhadap Pembiayaan Bank Syariah yang tidak menggunakan sistem bunga serta menganalisa dampak dari perubahan BI rate terhadap Bank Syariah. Penelitian ini mengambil data secara cross section berupa laporan keuangan Bank Syariah pada triwulan I tahun 2013 sebagai periode sebelum perubahan BI rate dan triwulan I tahun 2014 sebagai periode sesudah perubahan BI rate. Variabel yang digunakan yaitu total pembiayaan, rasio NPF sebagai gambaran kualitas pembiayaan dan pendapatan margin murabahah. Teknik pengumpulan data adalah melalui dokumentasi dan wawancara sebagai pendukung hipotesis penelitian. Sumber data yang diperoleh dari laporan keuangan publikasi Bank Syariah di situs resmi Bank Indonesia. Data dianalisis dengan menggunakan uji paired sample t test. Berdasarkan hasil penelitian diketahui bahwa terdapat perbedaan rata-rata total pembiayaan dan pendapatan margin murabahah bank syariah sebelum dan sesudah perubahan BI rate. Sedangkan tidak terdapat perbedaan rata-rata variabel NPF sebelum dan sesudah perubahan BI rate. Kata Kunci: BI rate, Pembiayaan, NPF, Margin Pembiayaan, Bank Syariah